Proximité entre riverains et pesticides en territoire de grandes cultures. Visibilité et invisibilité des micro-adaptations agricoles - Mathilde Hermelin-Burnol; Thibaut Preux (VertigO)
This article examines how the proximity of neighbouring populations (immediate residents and walkers) to pesticide treatments affects farmers' practices. We study the adaptations and adjustments that it induces over and above 2019's mandatory no-treatment zones (NTZ). We mobilize the complementarity between field work and spatial analysis by GIS at the scale of the urban area of Poitiers agricultural region of grain crops. This work is located in arable farming areas - a seldom studied area whose low spatial roughness may allow new forms of adaptation. We show that the scarcity of conflicts is however associated with tensions felt by the farmers. The temporal and spatial micro-adjustments observed reflect a desire to avoid contact with local residents during pesticide treatments. Eventually, these adaptations do not take the form of greening practices. In this context, pesticides are regarded as an agricultural nuisance. Thus, these adjustments mainly serve to anticipate locally feared tensions. They show that farmers consider the people living in the vicinity of their farms, sometimes on a very small scale.